ANALISIS PENGARUH JUMLAH UANG BEREDAR, SUKU BUNGA SERTIFIKAT BANK INDONESIA DAN SUKU BUNGA KREDIT INVESTASI TERHADAP INFLASI DI INDONESIA - Putri, Venny Kurnia; budiartiningsih, Rahmita; ', Rosyetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze how money supply, Bank Indonesia Certificate rate and investment interest rate affect the inflation. The data used in this study was a time series data from 2012 to 2016 were sourced from Bank Indonesia. This study used quantitative research methods, and analyzed by using multiple linear regression analysis by using SPSS 21 software program for Windows computers. In this study, the independent variable were Money Supply (X1), Bank Indonesia Certificates Rate (X2) and Investment Interest Rate (X3) while the dependent variable was Inflation (Y). The result showed the variable Money Supply, Bank Indonesia Certificates Rate and Investment Interest Rate at once / simultaneously had a significant influence on Inflation in Indonesia with significant rate 0.000. The individual test / partial showed that Money Supply had negative influence and significantly on Inflation in Indonesia. Bank Indonesia Certificates Rate had positive influence and significantly on Inflation in Indonesia. Investment Interest Rate had negative influence and significantly on Inflation in Indonesia Based on total R-Square result proved that on the variable money supply, Bank Indonesia Certificates rate and investment interest rate on inflation result of 73.3% while the rest of 26.7.0% were affect by other variables that were not performed in this study.Keywords: Money Supply, SBI rate, Investment Interest rate and Inflation